TEORI KE PRAKTIK: KONTRIBUSI FILSAFAT ILMU TERHADAP INOVASI MANAJEMEN PENDIDIKAN ISLAM - Kamila, Nadia Putri; Syandra, Syifa Hanifah; Fakhri, Jamal; Koderi, Koderi (Komunitas Manajemen Kompetitif, 2025)
This study aims to analyze the contribution of the philosophy of science to innovation in Islamic education management by highlighting the relationship between theoretical dimensions and institutional practices in responding to the challenges of globalization, digitalization, and value crises. Using the Systematic Literature Review (SLR) method, this research examines various national and international publications from 2019–2024 to identify integration patterns between the philosophy of science and managerial policies in Islamic education. The findings reveal that the philosophy of science serves as a conceptual, normative, and reflective foundation that guides Islamic education management to avoid technocratic and pragmatic tendencies. The ontological, epistemological, and axiological dimensions of the philosophy of science strengthen the formulation of vision, policy, and educational innovation that emphasize moral values, human development, and social benefit. However, the study also identifies a gap between philosophical ideals and managerial practices, which remain dominated by administrative efficiency. Therefore, reflective culture, value-based leadership, and management systems grounded in philosophical reasoning are needed to ensure that decision-making and innovation are ethically and spiritually guided. The results of this study are expected to enrich the theoretical and practical development of Islamic education management based on the philosophy of science and to offer a new direction for Islamic education as a civilizational force founded on knowledge, faith, and righteous action. Keywords: philosophy of science, Islamic education management, innovation, reflective leadership, educational reform